MORTALITAS LARVA NYAMUK Aedes aegypti DARI LIMA KELURAHAN DI KOTA BALIKPAPAN TERHADAP Temefos DAN Bacillus thuringiensis var. israelensis - Eka Kurnia Pratiwi; Nova Hariani (Jurnal Pro-Life, 2020)
Aedes aegypti Mosquito acts as a vector in infecting Dengue Haemorragic Fever (DHF). DHF is one of the healthproblems in Indonesia with high morbidity and large spreading that government has not found its solution. Oneof the strategies in controlling the vector is by using chemical larvacide such as Temefos. However, there isbiopesticide that developed recently by using Bacillus thuringiensis var. israelensis (Bti) bacterium. Balikpapancity is one of the endemic city of DBD with the high rank of cases in 2016 on 2.508 cases. Therefore, this researchis conducted to find out the mortality Aedes aegypti mosquito larvae from five areas (Batakan, Sepinggan, Damai,Muara Rapak, and Batu Ampar) in Balikpapan to Temefos and Bacillus thuringiensis var. israelensis. The methodof this research is Completely Randomizd Design. Steps of this research are observation, collecting sample,documentation, monitoring, and data tabulation. This result of this research is the mortality of Aedes aegypti infive areas in Balikpapan to Temefos during 24 hours by using recommended concentration from the government1 ppm in four areas (Batakan, Damai, Muara Rapak, Batu Ampar) is above 90% and from Sepinggan is under90%. Meanwhihle, the mortality of Aedes aegypti toward Bacillus thuringiensis var. israelensis during 24 hoursby using recommended concentration from the government 20 ppm in three areas (Muara Rapak, Damai, BatuAmpar) is above 90% and two areas (Batakan dan Sepinggan) is under 90%. The result showed that Temephos isnot recommended to control population of mosquitos of Aedes aegypti in Balikpapan City but Bacillus thuringiensivar. israelensis (Bti) is still effective be used to control it.Keywords: Mortality, Aedes aegypti, DHF, Balikpapan